The Difference in The Activity of Ethanol Extracts of Leaves of Anti Diabetic tin (Ficus Carica l.) Leaf, Rambutan (Nephelium Lappaceum) and Persimmon (Diospyros Ft L) on The White Mancit on Streptozotocin Induced - Nurlinawati; Kamariyah; Yosi Oktarina; Sri Mulyani (Talenta Publisher, 2019)
Diabetes mellitus is a metabolic syndrome most public figures around the globe with events 1-8%. This disease occurs when insulin in insulin production or tidakcukup may not function properly or the amount of insulin enough but it works less well characterized by high levels of sugar in the blood. The Research Design used in this research is experimental design pre test and post test design group, where only when the post test (end) only performed measurements. Research use only post test where observations are conducted as many as 3 times at the time after thera-py/experiment. Observations made after experiment (X 2) called the Post Test. It is known that a group of white male mice strain spreague dawley fed leaves etha-nol extract rambutan (Ficus carica l.), shows a decrease in blood sugar levels better when compared to the Group of esktrak penginduksi with a persimmon the same form of induction of streptozoto-cin. Ethanol extracts of leaves of Rambutan (Nephelium lappaceum) Note can lower the blood sugar levels of 9 mg/dl and persimmon (Diospyros ft L) can lower the blood sugar levels of 5.3 mg/dl, while the leaves of Tin (Ficus carica l.) showed can increase blood sugar levels in mice white male spreague dawley strain induced streptozotocin.Keyword: self-acceptance, chronic kidney failure, hemodialysis.